2011
DOI: 10.1039/c0jm02683b
|View full text |Cite
|
Sign up to set email alerts
|

Green chemical decoration of multiwalled carbon nanotubes with polyoxometalate-encapsulated gold nanoparticles: visible light photocatalytic activities

Abstract: both reducing, encapsulating molecules and bridging molecules, and avoid introducing other organic toxic molecules. Most importantly, the prepared nanohybrids have been found to have enhanced photocatalytic activities under visible light irradiation. The synergistic effect of the three components in the nanohybrids leads to the enhanced photocatalytic property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 27 publications
1
64
0
Order By: Relevance
“…15. HRTEM investigation reveals that hexagonal ZnO nanorods ‘with pencil like tip’ are crosslinked together by PMA anions 148 and self-assembled to nanoplatelets with grain boundaries as shown in Fig. 15(a 1,2 and b 1,2,3 ).…”
Section: Catalytic Deposition Mechanismmentioning
confidence: 99%
“…15. HRTEM investigation reveals that hexagonal ZnO nanorods ‘with pencil like tip’ are crosslinked together by PMA anions 148 and self-assembled to nanoplatelets with grain boundaries as shown in Fig. 15(a 1,2 and b 1,2,3 ).…”
Section: Catalytic Deposition Mechanismmentioning
confidence: 99%
“…POMs have the unique ability to implement stepwise redox reactions while keeping their structure mainly unchanged. Once reduced, POMs such as [SiW 12 [179] efficiently transfer electrons to Au(III) therefore producing Au-NPs (see Fig. 9).…”
Section: Metal Complexes and Inorganic Systemsmentioning
confidence: 98%
“…[14,15] The morphology of the AuNP-s@POMD was characterized by TEM (Figure 1), and the size distribution is shown in Figure S1 (Supporting Information). First, POMDs were readily grafted on the surface of AuNPs via a one-step synthetic route.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 1 B, the 1.35 nm-thick shell consists of a monolayer of POMD anions (Supporting Information, Figure S1B). [14,15,21] Subsequently, the N-acetyl-Cys-LPFFD peptide (N-Ac-CLPFFD) was conjugated to the AuNPs through the cysteine thiol group in 10:1 molar ratio with the AuNPs. The TEM image revealed that AuNPs@POMD was surrounded by a monolayer of POM anions.…”
Section: Resultsmentioning
confidence: 99%